Web site measurement hacks - Peterson, Eric T. (O'Reilly, 2005)
In order to establish and then maintain a successful presence on the Web, designing a creative site is only half the battle. What good is an intricate Web infrastructure if you're unable to measure its effectiveness? That's why every business is desperate for feedback on their site's visitors: Who are they? Why do they visit? What information or service is most valuable to them? Unfortunately, most common Web analytics software applications are long on functionality and short on documentation. Without clear guidance on how these applications should be integrated into the greater Web strategy, these often expensive investments go underused and underappreciated. Enter Web Site Measurement Hacks, a guidebook that helps you understand your Web site visitors and how they contribute to your business's success. It helps organizations and individual operators alike make the most of their Web investment by providing tools, techniques, and strategies for measuring--and then improving--their site's usability, performance, and design. Among the many topics covered, you'll learn: definitions of commonly used terms, such as "key performance indicators" (KPIs) how to drive potential customers to action how to gather crucial marketing and customer data which features are useful and which are superfluous advanced techniques that senior Web site analysts use on a daily basisBy examining how real-world companies use analytics to their success, Web Site Measurement Hacks demonstrates how you, too, can accurately measure your Web site's overall effectiveness. Just as importantly, it bridges the gulf between the technical teams charged with maintaining your Web's infrastructure and the business teams charged with making management decisions. It's the technology companion that every site administrator needs.